Students’ Perception and Acceptance of “ELSA” to Improve Pronunciation Skill - Akriono, Farah Khairani; Isnaini, Moh Hasbullah (Universitas Pahlawan Tuanku Tambusai, 2024)
Pronunciation is important for effective communication. However, many learners still struggle with pronunciation skills. In the 4.0 technology era, artificial intelligence (AI) technology can be used, such as the ELSA Speak application. While previous studies have highlighted the effectiveness of the technology itself, it pays less attention to students’ perceptions of the application’s use as an independent learning medium. This research aims to investigate students’ perception and acceptance of ELSA technology as an independent learning medium for improving pronunciation skills. This qualitative approach used a case study design. The researchers utilized semi-structured interviews for data collection, which focused on perceived usefulness and perceived ease of use. Students stated that ELSA is useful in improving students’ pronunciation skills through effective learning. With its user-friendly application, ELSA supports the learning process effectively. Thus, students positively perceive the usefulness and user-friendliness of the ELSA to improve their pronunciation skills.